Optimizing Recruitment and Selection Processes at ATM Recruitment Consultancy (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This study evaluates the effectiveness of the recruitment and selection process at ATM Recruitment Consultancy and offers advanced technologies and methods to identify the most suitable candidates. Its findings aim to help the recruitment team refine policies and procedures to enhance both efficiency and effectiveness. By integrating theoretical insights with practical investigation, the project provides ATM Recruitment Consultancy with data-driven recommendations. The research focuses exclusively on the Human Resource Department’s recruitment and selection function. The primary objective is to examine current practices, while secondary objectives include assessing employer perceptions of various recruitment sources, evaluating interview and final selection discussions, reviewing employee views on medical testing quality and technical interviews, and gauging satisfaction with compensation features. Responses from 110 employees were gathered using convenience sampling and multiple-choice questionnaires. Data analysis employed statistical tools such as Karl Pearson’s Correlation, Chi-square tests, and one-way ANOVA. The research revealed key insights into candidate sourcing, interviewer effectiveness, and selection protocols. Based on these findings, several targeted suggestions are provided to strengthen Consultancy’s overall recruitment and selection framework.